2019
DOI: 10.1007/s10519-018-9943-x
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Cultural Inheritance Enhance Agency, but What are the Origins of this Concern to Establish a Legacy? A Nationally-Representative Twin Study of Erikson’s Concept of Generativity

Abstract: Generativity—showing concern to establish and guide future generations—has been argued to be a biological adaptation central to cumulative culture and survival, but also, in turn, to be a cultural adaptation dependent on norms. From the perspective of human agency, concern for the future has played a key role in raising agency for generations that follow by creating infrastructure and cultural inheritance. Here, in a population-representative sample of 756 twin-pairs, we present the first test of the genetic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 83 publications
(129 reference statements)
0
6
0
Order By: Relevance
“…In Study 2, we replicate this structural model in an independent dataset, assuring ourselves that this structure is replicable. In Study 3, we apply this new three-factor structure to a representative twin sample, modeling the genetic and environmental influences on each factor to resolve the questions of genetic and environmental causation left open in Fassbender et al (2019).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 3 more Smart Citations
“…In Study 2, we replicate this structural model in an independent dataset, assuring ourselves that this structure is replicable. In Study 3, we apply this new three-factor structure to a representative twin sample, modeling the genetic and environmental influences on each factor to resolve the questions of genetic and environmental causation left open in Fassbender et al (2019).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Einolf (2014) himself predicted that desire to form a legacy would likely form a separate factor if the full LGS was used. Surprisingly, in a twin study capable of revealing differential transmission of the items, Fassbender et al (2019) found that three distinct factors were required to account for the patterns of family transmission in the short scale: (1) a general factor of concern for the future, (2) a factor of feeling oneself to be a valued source of advice and assistance for others and (3) a factor involving being a good influence on the lives of others. This multifactorial structure suggested to us that, in the full LGS scale, the multicomponential descriptions of generativity described by Kotre and Kotre (1984), and Erikson (1963) would emerge.…”
Section: Study 1: Testing the Phenotypic Structure Of Generativitymentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from a genetic component (Faßbender et al, 2019), research has identified family factors that contribute to an individual's generativity development. For example, parents' authoritative parenting style is positively associated with their adult offspring's generativity (Peterson et al, 1997).…”
Section: The Development Of Generativitymentioning
confidence: 99%